Designing for change in networked learning environments : proceedings of the International Conference on computer support for collaborative learning - Wasson, Barbara; Ludvigsen, Sten; Hoppe, Ulrich, 1954- (Dordrecht : Kluwer Academic Pubs, 2003)
44